A novel approach to assess the ubiquitin‐fold modifier 1‐system in cells. Issue 1 (20th December 2016) - Ishimura, Ryosuke; Obata, Miki; Kageyama, Shun; Daniel, Jens; Tanaka, Keiji; Komatsu, Masaaki
Abstract : The ubiquitin‐fold modifier 1 (UFM1)‐system, a ubiquitin‐like protein conjugation system, is involved in the development of breast cancer and several hereditary neurological syndromes. However, the molecular mechanisms of UFM1‐related pathogenesis remain unclear. Here, we show that in the absence of UFSP2, a deconjugating enzyme for UFM1, ectopic expression of both UFL1 and UFBP1, which serve as the E3‐ligase complex for the UFM1‐system, dramatically increases UFM1‐conjugate formation at the endoplasmic reticulum. Utilizing this system, we were able to attribute disease‐related isoforms of UBA5, the E1 enzyme for UFM1, to decreased UFM1‐conjugate formation. Our procedure allows the assessment of UFM1‐conjugate formation in cells and the identification of UFM1‐targets, both of which are needed to clarify the pathophysiological role of the UFM1‐system. Abstract :